SURVEY TINGKAT KETERAMPILAN DASAR FUTSAL DAN VO2MAX SISWA EKSTARKURIKULER FUTSAL SMA NEGERI 5 PONTIANAK - Ardiansyah, Ryan; Triansyah, Andika; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this study was to determine the Basic Skills Level of Futsal and Vo2max Futsal Extrarkuricular Students of SMA Negeri 5 Pontianak. The study was conducted with the method used in this study was a descriptive method, aimed at finding out the basic skills level of futsal and the physical condition of futsal extracurricular students at SMA Negeri 5 Pontianak. The population in this study was the futsal extracurricular students of SMA Negeri 5 Pontianak, totaling 40 students, with a sample of 40 students. This research technique uses tests and measurements, namely tests with a lattice measuring instrument measuring the basic skills of playing futsal and the ability of VO2Max Students. Data analysis using percentages. The results of the study concluded that the Futsal and Vo2max Basic Skills Level of Futsal Extra-curricular Students of SMA Negeri 5 Pontianak were included in the Fair category. Where the results of the basic skills test playing futsal futsal extracurricular participants at SMA Negeri 5 Pontianak are presented in the form of frequencies (percent).